Analysis of Hemostasis Function in Obesity Subjects Using Thromboelastography - Kasimat, Maria Magdalena; Nurahmi, Nurahmi; Kurniawan, Liong Boy (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Hemostasis disorders can be caused by obesity, associated with decreased fibrinolysis, increased fibrinogen and plasminogen activator inhibitor activity. Thromboelastography shows hemostasis function from clots formation to the fibrinolysis process. This study aimed to determine the hemostasis function in obese compared to non-obese subjects using thromboelastography. A cross-sectional study at the Clinical Pathology Laboratory Installation of Dr. Wahidin Sudirohusodo Hospital. The study population was non-diabetic subjects who agreed to participate. Hemostasis tests using thromboelastography and analysis of R, K, Alpha angle, and Maximum Amplitude (MA) values were performed. The total number of research subjects was 40 subjects, consisting of 20 obese subjects and 20 non-obese subjects. In these two groups, there were no differences in the K (2.92±1.3 vs. 2.64±1.1, p=0.461), Alpha angle (54.18±9.2 vs. 56.29±10.5, p=0.372), and MA values (57.99±10.3 vs. 54.93±8.2, p=0.766). The obese group got a higher R-value than the non-obese group (7.45±1.8 vs. 4.11±1.2. p=0.006) The R-value was higher (elongated) in the obese subject than the non-obese subject. In the two subject groups, there were no differences in the K, Alpha angel, and MA values.